„Przybywaj, ogniu!” Szkic o historii polskich tłumaczeń dzieł Friedricha Hölderlina - Maryjka, Wojciech (Wydawnictwo Uniwersytetu Rzeszowskiego, 2020)
The article of Wojciech Maryjka presents the development of Polish translations of the works of the German poet, writer and philosopher, Friedrich Hölderlin, whose 250th birthday anniversary falls on 20 March 2020. The author of the text provides the reasons why Hölderlin evoked interest in the Polish literature rather late. He indicates a significant role of translations of Stefan Napierski dated 1937 and 1938, but he noted that also Leo Belmont had translated several of Hölderlin’s poems earlier, in 1900. Further in the article, the researcher highlights the significance of the Selected Poems by Hölderlin published in 1964 that had been translated into Polish by Mieczysław Jastrun. Maryjka also indicates the significance of the pioneer monograph of the life of Hölderlin written by Zdzisław Żygulski. Further in the study, volumes of Hölderlin’s poetry are discussed, as translated by Bernard Antochewicz, Andrzej Pańta, Antoni Libera and Andrzej Lam, who had been the first who translated all poems of the German poet. The author of the article did not skip other works that contributed to exploration of the works and life of Hölderlin in Poland including, inter alia, the fictionalized biography entitled Hölderlin by Peter Härtling, translated by Sława Lisiecka, or the volume containing Hölderlin’s letters and his Hyperion prepared by Anna Milska and Wanda Markowska.
“Fire, come forth!”. On the History of Polish Translations of Writings by Friedrich Hölderlin
Keywords: Friedrich Hölderlin; Polish Translations; recepcion; poetry; polskie tłumaczenia; recepcja; poezja